Genetic diversity of exotic and local eggplants (Solanum spp.) cultivated in Côte d’Ivoire based on ISSR markers - N'Guessan Olivier Konan; MARIE ANGE AKAFFOU; LÉONARD KOUADIO; DOFFOU SÉLASTIQUE AKAFFOU; GUY MERGEAI (Society for Indonesian Biodiversity, 2020)
Abstract. Konan NO, Akaffou MA, Kouadio L, Akaffou DS, Mergeai G. 2020. Genetic diversity of exotic and local eggplants (Solanum spp.) cultivated in Côte d’Ivoire based on ISSR markers. Biodiversitas 21: 3651-3658. Eggplants are important vegetables in Côte d'Ivoire. Despite an increase in the cultivation of exotic genotypes and their progressive dominance over local cultivars, which could represent a threat of genetic erosion, there are not enough molecular data available on the genetic diversity of the eggplants currently cultivated in this country. This study is a contribution to the knowledge of the genetic diversity of the current eggplant cultivars grown in Côte d’Ivoire. It aimed to assess the genetic variation of nine exotic and local eggplants commonly cultivated in Côte d'Ivoire, using five inter-simple sequence repeat (ISSR) primers. The results revealed for the exotic cultivars 42 ISSR loci of which 31 were polymorphic (73.81 %), and for local cultivars 51 loci of which 49 (96.08%) were polymorphic. The Nei’s genetic diversity and Shannon’s information index of local cultivars (He = 0.3333 and I = 0.4863) were higher than those of exotic cultivars (He = 0.2000 and I = 0.2971). The Gst value and the AMOVA analysis found more than 70% of the total genetic diversity within the groups. The Jaccard’s dissimilarity coefficients between the cultivars, ranged from 0.324 to 0.966 with an average of 0.741. The clustering of genotypes with the neighbor-joining unrooted tree and PCoA analysis differentiated three main clusters with exotic cultivars grouped in cluster I and local cultivars in cluster II and III. In view of these results, the local eggplants had higher genetic diversity and constitute an interesting germplasm which needs to be conserved for potential breeding programs.